Evaluation of the Effects of Sand Sachet Materials on Efficacy of Temephos Sand Granules against Aedes aegypti L. Larvae - Sripho, Wisachon; Sathantriphop , Sunaiyana; Sumarnrote, Anchana; Kongmee , Monthathip (Disease Control Journal, 2026)
The use of temephos sand granules for the control of Aedes aegypti larvae is a widely accepted and effective method. One application form of this larvicide is the ready-to-use sand sachet. However, based on bioefficacy data from 2016 to 2022, none of the sachet-based products fulfilled the standard criteria set by the Department of Medical Sciences. Therefore, this study aimed to evaluate the structure and properties of various materials, to select the optimum material for the sand sachets, and to compare two testing equipment for ensuring adequate larval bioefficacy. Sand sachet packaging made from various materials were selected and filled with 1% w/w temephos sand granules at a concentration of 1 ppm for testing. Two types of observation equipment were used: floating larval cages and free-living larval cages. Based on initial material evaluations, one commercially available sachet and one alternative sachet made of nylon were selected for comparative testing under simulated natural conditions. Larvicidal efficacy was assessed 24 hours post-exposure, following periods of 24 hours, 7 days, and every 30 days up to 180 days after temephos application. The results showed that the 24-hour larval mortality rate from sachets made with commercial materials after 24 hours and 7 days of applying was the lowest among all test treatments. From 24 hours to 120 days after application, the 5 g nylon sachets (4 sachets) demonstrated larvicidal efficacy comparable to that of 20 g of unpackaged temephos-treated sand (positive control), followed by the 20 g nylon sachets. Furthermore, from 90 days onward following the application of all forms of temephos-treated sand, a statistically significant difference (p<0.05) in larval mortality was observed between the two types of test equipment, with free-living larval cages showing higher mortality rates than floating larval cages. These findings suggest that nylon is the most suitable material for use as packaging for temephos sand granules. Additionally, the use of free-living larval cages enhances the effectiveness of bioassay evaluations under simulated natural conditions.